Advances in the role and mechanism of lactic acid bacteria in treating obesity. Issue 1 (27th March 2022) - Shen, Yi‐Lin; Zhang, Liu‐Qing; Yang, Ying; Yin, Bin‐Cheng; Ye, Bang‐Ce; Zhou, Ying
Abstract: Obesity and its related complications have become increasingly serious social problems that threaten people's lives. Lactic acid bacteria (LAB) have shown an effective influence on preventing obesity in animal experiments and human clinical trials, but its exact mechanism remains unclear. In this review, LAB and several of its metabolites are taken as the point of penetration. It is aimed to summarize the relationship between obesity and gut microbiota, the efficacy of LAB, and its potential mechanisms of preventing obesity and lipid metabolism. LAB intervention can regulate gut microbiota and improve intestinal permeability which is damaged by a high‐fat diet or lipopolysaccharide. Besides this, some metabolites produced by LAB can be involved in regulating host lipid metabolism‐related pathways. Short‐chain fatty acids, linoleic acid, and gamma‐aminobutyric acid, taken as representatives here, can participate in the regulation through AMP‐activated protein kinase or peroxisome proliferator‐activated receptor pathway and bowel–brain axis. Therefore, the ingestion of LAB may become a potential adjunctive treatment for obesity in future. Abstract : The antiobesity effect of lactic acid bacteria (LAB) connects with several regulatory factors, including intestinal microbiota, intestinal tract, metabolism in adipose tissues, and the central nervous system of the brain. A variety of metabolites derived from LAB may play a crucial regulatory role in the energy and fat metabolism‐related signaling pathways of the host, including AMP‐activated protein kinase, peroxisome proliferator‐activated receptor, and other classical signaling pathways.